Secondary Nerve Lengthening to Obtain Full Knee Extension in Popliteal Pterygium Syndrome - Boeckx, Willy; Misani, Marta; Vandermeeren, Liesbeth; Franck, Diane; Zirak, Christophe; Demey, Albert (Journal of Reconstructive Microsurgery, 2014)
Microsurgical nerve lengthening was performed in two siblings presenting a popliteal pterigium syndrome with a knee flexion contracture of 80 degrees. After the first attempt for nerve lengthening and knee extension elsewhere, a repeated lengthening was required due to continuing tip-toe walking and recurrent knee contracture at the age of 3 years. An extensive external and internal interfascicular microsurgical neurolysis resulted in a lengthening of the nerves. A full length of leg procedure had to be performed, inclusive of Achilles tendon lengthening to obtain a complete extension of the knee and a 90-degree ankle flexion. Maintaining the leg in a fully extended position was obtained with a dynamic splinting in the first month after the operation. When timing the operation we have to consider the importance of adequate precision of the microsurgical neurolysis, down to the identification of the Fontana bands, and the adequate postoperative splinting.
Keywords: internal neurolysis; congenital; nerve contracture; popliteal webbing; microsurgery